Emilia Pardo Bazán ante el fin de siglo. Edición de “Eduardo Rod. El Pensador” - López Quintáns, Javier (2015)
The work deals with the literary change in the last decades of the nineteenth century (in the literary production of Emilia Pardo Bazán) from the Naturalism to the Spiritualism. Emilia Pardo Bazán published several works about Rod, representing the new trend. We publish “Escritores franceses contemporáneos: Rod”.